Measurement of Local Government Financial Performance in Palopo City using The Concept of Value For Money - Salsabila, Nurul; Pratiwi, Indah; Dasila, Rifqa Ayu (Journal of Applied Business, Taxation and Economics Research, 2025)
Regional government financial management has an important role in improving public services and supporting development. Good financial performance reflects effective, efficient and economical use of the budget. One method that can be used to measure performance is the value for money concept which focuses on three main aspects: economy, efficiency and effectiveness. This research aims to measure the financial performance of the Palopo City Government during the 2019-2023 period using the Value for Money concept. The method used is a quantitative descriptive approach with descriptive statistical analysis, using APBD data and APBD Realization from the Reagional Financial and Asset Management Agency (BPKAD) OF Palopo City. Data is collected through official documents published by local governments, which are then analyzed to assess the extent to which budget use meets the principle of economics, efficiency and effectiveness. The research results show that the economic performance and efficiency of the Palopo City Government is generally in the quite good category, although there are fluctuations from year to year. The effectiveness ratio tends to decrease from year to year, indicating a gap between planning and actual income.